2011
DOI: 10.4321/s0004-05922011000300049
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Albanian goat breeds based on microsatellite markers

Abstract: SUMMARYThe domestic goat is one of the most important livestock species in mountainous area of Albania. In this study thirty microsatellite markers in 183 unrelated individuals from 6 local goat breeds are analyzed. Twenty nine markers had five or more alleles. All loci were polymorphic and a total of 331 alleles were detected. The average number of alleles per locus was 11.03. Within breeds, the mean number of alleles ranged from 7.8 to 8. Mean expected heterozygosity (He) . La consaguinidad para toda la pob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
(14 reference statements)
3
9
1
Order By: Relevance
“…It was suggested that less inbreeding values of less than 0.5 or closer to zero (Wang, 1996) might have happened due to the absence of mating between close relatives and/or within individuals. Similarly, such comparable inbreeding values were also reported for Asian (Barker et al, 2001), Indian goat populations (Kumar et al, 2005;Aggarwal et al, 2007;Dixit et al, 2008;Dixit et al, 2010) and local Albanian goat breeds (Hoda et al, 2011). The HWE test results revealed that most of the markers used to study Syrian goats were not in HWE, except one locus (that is, ETH10) did show adherence to HWE for Jabali goats (Table S1).…”
Section: Genetic Diversity and Differentiationsupporting
confidence: 74%
“…It was suggested that less inbreeding values of less than 0.5 or closer to zero (Wang, 1996) might have happened due to the absence of mating between close relatives and/or within individuals. Similarly, such comparable inbreeding values were also reported for Asian (Barker et al, 2001), Indian goat populations (Kumar et al, 2005;Aggarwal et al, 2007;Dixit et al, 2008;Dixit et al, 2010) and local Albanian goat breeds (Hoda et al, 2011). The HWE test results revealed that most of the markers used to study Syrian goats were not in HWE, except one locus (that is, ETH10) did show adherence to HWE for Jabali goats (Table S1).…”
Section: Genetic Diversity and Differentiationsupporting
confidence: 74%
“…The F ST analysis indicated that 98.7% of the variation was found within the goat breeds and only 1.3% ( P = 0.039) among them. These results show a low level of breed differentiation and are in concordance with the results obtained previously for the same goat breeds, using microsatellites,[ 19 ] SNP [ 20 ] and AFLP. [ 21 ] Table 2 represents the pairwise F ST values among breeds with their significance levels.…”
Section: Resultssupporting
confidence: 91%
“…; Hoda et al . ), pig (Fan et al . ), horse (Bjornstad & Roed ), dog (Toskinen & Bredbadka ), poultry and rabbit (Gotz & Thaller ).…”
Section: Training and Testing Performances Of Various Modelsmentioning
confidence: 99%